Kings and cults : state formation and legitimation in India and Southeast Asia - Kulke, Hermann (New Delhi : Manohar Publishers & Distributors, 1993)
Articles covers medieval India and Southeast Asia.
Includes bibliographical references and index.
Keywords: Cults -- India; Cults -- Southeast Asia; India -- History -- 1000-1526.; India -- History -- 1526-1765.; Southeast Asia -- History